Аспекты психолого-педагогической адаптации мигрантов и овладения иностранным языком - Бауэр, Елена А.; Кабардов, Мухамед К. (International Dialogues on Education Journal, 2014)
This article deals with selected aspects of migrants’ psycho-social adaptation and with processes of foreign-language proficiency. Adjustment to a new culture involves the loss of home and social relationships and typically causes stress. Lack of proficiency in another language has an additional negative effect on the psyche of migrants and, eventually, on the process of adaptation to the new sociocultural context. The authors’ study shows the necessity of considering typical and individual characteristics of migrants learning the language of the receiving country.